Advanced exergy and exergoeconomic analysis of an integrated system combining CO2 capture-storage and waste heat utilization processes. (15th March 2021) - Wang, Yinglong; Chen, Zhengrun; Shen, Yuanyuan; Ma, Zhaoyuan; Li, Huiyuan; Liu, Xiaobin; Zhu, Zhaoyou; Qi, Jianguang; Cui, Peizhe; Wang, Lei; Ma, Yixin; Xu, Dongmei
Abstract: To solve the problem regarding the purification of coal syngas, a system that integrates the CO2 capture and storage process and the waste heat utilization processes is proposed herein and analyzed using advanced exergy and exergoeconomic analysis methods. The purpose is to obtain the distribution of the exergy destruction rate and the cost rate of each block in the integrated process. The total exergy efficiency of the system was found to be 17.56%. Moreover, the total exergy destruction was 36424 kW, of which the CO2 capture and storage process accounted for 43.15%, the organic Rankine cycle process accounted for 32.35%, and the absorption refrigeration cycle process accounted for 24.50%. The exergy destruction ratio of the whole system was 82.44%. In this process, the optimization of the blocks such as the distillation column, absorber, and Evaporator 2 is to be considered a priority. Advanced exergy and energy efficiency analysis can provide guidance for the optimization of system irreversibility and help to determine the improvement potential of each block. In addition, certain strategies are proposed for the improvement of each block on the basis of the results, which can provide a theoretical flowchart for the efficient operation of the integration process. Highlights: Advanced exergy and exergoeconomic analyses are used to evaluate integration process. The total exergy efficiency of the system was found to be 17.56%. The CO2 capture and storage process accounted for 43.15%. The absorption refrigeration cycle process accounted for 24.50%. Three strategies are proposed to help improve the integration process.